A comprehensive review of tire-pavement noise: Generation mechanism, measurement methods, and quiet asphalt pavement. (10th March 2021) - Ling, Senlin; Yu, Fan; Sun, Daquan; Sun, Guoqiang; Xu, Lei
Abstract: As the main source of traffic noise, tire-pavement noise poses a major threat to human health. Reducing tire-pavement noise influences of quality of life has recently drawn increasing attention. Quiet asphalt pavement provides an effective method to reduce tire-pavement noise and achieves economic, social and environmental benefits, due to take advantage of the existing infrastructure and combines the function of reducing noise. Tire-pavement noise generation mechanisms, tire-pavement noise measurement methods, the noise reduction mechanism of pavement, and some common and novel quiet asphalt pavement are reviewed in this paper. The paper reveals that tire air-pumping noise is the main source of tire-pavement noise. The existing tire-pavement noise measurement methods need to be further perfected to improve the accuracy of measurement results. All quiet asphalt pavements have good noise reduction performance, but each has its suitable range of applications. The purpose of this review is to provide reference and guidance for researchers to measure the tire-pavement noise, design quiet asphalt pavement, and select suitable quiet pavement according to the local conditions.